Thermoresponsive polymer system based on poly(N-vinylcaprolactam) intended for local radiotherapy applications - Černoch, Peter; Černochová, Zulfiya; Kučka, Jan; Hrubý, Martin; Petrova, Svetlana; Štěpánek, Petr (Applied radiation and isotopes, 2015)
Brachytherapy represents effective local therapy of unresectable solid tumors with very few side effects. Radiolabeled thermoresponsive polymers offer almost noninvasive approach to brachytherapy applications. A radioiodinated, water-soluble, thermosensitive poly(N-vinylcaprolactam) (PVCL) polymer was prepared using two approaches. The direct copolymerization with N-methacryloyl-l-tyrosinamide, as well as end-capping of carboxy-terminated PVCL homopolymer with tyramine, were used. In both cases the product was successfully radiolabeled with (125)I. The obtained polymers demonstrate cloud-point temperature (TC) values in the range of 33-35°C in all the studied solvent systems (water, PBS (pH 7.4) and physiological saline solution). Above the cloud point temperature, the molecularly dissolved polymer is macroprecipitated from the solution. The TC values close to the human body temperature of this biocompatible poly(N-vinylcaprolactam) polymer makes it a promising material intended for local therapy of solid tumors.
Keywords: Biocompatible Materials; Caprolactam; methakryláty; lidé; voda; kaprolaktam; Methacrylates; biokompatibilní materiály; Poly(N-vinylcaprolactam); Water; radioizotopy jodu; tyrosin; brachyterapie; Neoplasms; Polymers; Tyrosine; Tumor; Humans; Temperature; nádory; Brachytherapy; Thermosensitive polymer; Solubility; testování materiálů; polymery; rozpustnost; Materials Testing; Iodine Radioisotopes; teplota